Carga epidemiológica da coqueluche e avaliação de impacto de vacinação de gestantes contra coqueluche implementada no Brasil em 2014 - Bagattini, Ângela Maria (2022)
Introduction: Pertussis is an acute infectious disease of respiratory transmission, with cyclical occurrence, it is endemic worldwide, represents an important global burden, particularly in children under one year of age who have more severe conditions and may progress to death. Between 2010 and 2014, a sudden and atypical increase in the number of cases of the disease was observed in several countries, including Brazil. There are several hypotheses about the factors associated with this resurgence, including disease cyclicality, replacement of whole-cell vaccines with acellular vaccines, falling vaccine coverage in children, and the effectiveness and duration of protection of vaccines in children, among others. Objectives: This study aims to characterize and estimate the epidemiological situation of pertussis in Brazil, evaluate the impact of vaccination of pregnant women with pertussis vaccine (dTpa) implemented in Brazil in 2014. Also, review the evidence about protection and duration of protection conferred by the whole cell vaccine against pertussis used for vaccination of children in the National Programs of Immunization. Methods: A study in three stages was carried out. The first stage described the epidemiological situation of whooping cough in morbidity and mortality in Brazil from 2000 to 2016. Next, the second stage with an interrupted time series ecological study was carried out with data adjusted by month and using the ARIMA model to assess the impact on cases and hospitalizations of children under five years of age with the introduction of the dTpa vaccine for pregnant women in 2014. The two stages used three independent health information systems, the Information System for Notifiable Diseases (SINAN), the Hospital Information System (SIH), the Mortality Information System (SIM) and the National Immunization Program Information System (SI-PNI), data were aggregated and evaluated by age group and federation unit. The third stage of the study was carried out through a systematic review to assess the effectiveness and duration of protection provided by the whole cell pertussis vaccine (DTPw) in children considering the vaccines currently available on the international market. Results: Pertussis showed cyclical patterns of disease burden over time between 2000 and 2016 in Brazil, in different regions with heterogeneous conditions, with a well-defined outbreak that started in 2011 and peaked in 2014, reaching mainly and more severely. children under six months, with 20,103 (54%), 19,919 hospitalizations (79%) and 565 deaths (93%). The incorporation of dTpa vaccination in pregnant women was associated with a significant reduction in pertussis cases and hospitalizations in children under six months of age when coverage is above 45%. After the introduction of dTpa, it is estimated that 2,124 cases and 1,439 hospitalizations for pertussis were avoided in children under six months of age in states with coverage above 45% between 2015 and 2016. Additionally, 12 studies with DTwP conducted between 2007 and 2020 were included for review, which have varied methodological quality and lack evidence on immunogenicity and duration of immunity indicating a short duration, less than five years. Conclusions: The analysis of different health information systems used showed consistent results throughout the period analyzed, reflecting the cyclicity of the disease and its resurgence from 2011. The incorporation of dTpa vaccination in pregnant women resulted in an impact on the reduction of hospitalizations and deaths of children when vaccination coverage above 45% is achieved. The wP vaccines currently in use have scant evidence of duration of immunity, even though they are used in over 100 countries, in most low- and middle-income countries. Relevance and Impact: The results of this work reinforce the importance of achieving and maintaining dTpa vaccination coverage in pregnant women above 45% in order to obtain a significant impact of vaccination of pregnant women in reducing hospitalizations for pertussis in children. Although wP is one of the most used vaccines globally in children in immunization programs in low- and middle-income countries, there has been an important change in the producers of these vaccines in recent decades, with large pharmaceutical companies having left the market and being replaced by producers in countries emerging technologies that today account for the totality of wP vaccines produced and used in the world. Evidence suggests that the duration of protection afforded by these vaccines in children is short. However, better quality evidence on the effectiveness and duration of immunity conferred by these vaccines is needed to support the definition of more appropriate vaccination strategies.